Developing a Sustainable Design-Based Creative Board Game to Enhance Children’s Creativity and Maritime Awareness - Anda Iviana Juniani; Putri Amelia; Dika Rahayu Widiana; Wiediartini Wiediartini; Widya Emilia Primaningtyas; Khoirul Amin; Rizal Indrawan; Rifqi Abid Maulana; Rabbani Budi Santosa; Dhandys Ayu Juli Anjhani; Dava Khilla Kurniawan (Journal of Innovation and Community Engagement, 2026)
Creativity is an important 21st century competency in which instructional media must be able to stimulate flexible thinking and meaningful problem solving. Board games offer significant pedagogical potential by integrating playfulness with structured cognition. However, most of the commercial board games still use plastic-based materials, which raises concern about the environmental sustainability, especially in the context that is affected by plastic pollution. To address this gap, the present study developed a creative board game with a maritime environmental awareness theme using the Design for Sustainability (DfS) approach, ensuring dual pedagogical value that fostering children’s creativity while embedding ecological responsibility through sustainable material and design. The Research and Development (R&D) method following the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) stages of the ADDIE model. Validation results showed feasibility scores of 89%, based on media experts, and 88%, based on material experts, which are both in the "highly feasible" category. These findings validate the board game as a sound medium for stimulating creativity and ecological awareness. Future research should implement and evaluate the tool with children to provide empirical evidence of its effectiveness.